2015
DOI: 10.1007/s10578-015-0551-1
|View full text |Cite
|
Sign up to set email alerts
|

The Social Appearance Anxiety Scale in Italian Adolescent Populations: Construct Validation and Group Discrimination in Community and Clinical Eating Disorders Samples

Abstract: Anxiety in situations where one's overall appearance (including body shape) may be negatively evaluated is hypothesized to play a central role in Eating Disorders (EDs) and in their co-occurrence with Social Anxiety Disorder (SAD). Three studies were conducted among community (N = 1995) and clinical (N = 703) ED samples of 11-to 18-year-old Italian girls and boys to (a) evaluate the psychometric qualities and measurement equivalence/invariance (ME/I) of the Social Appearance Anxiety (SAA) Scale (SAAS) and (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 65 publications
(230 reference statements)
9
38
1
5
Order By: Relevance
“…Since the current investigation indicates fear of negative evaluation is a particularly important social anxiety facet to consider in relation to disordered eating symptoms for youth with obesity, additional research must begin to examine similar constructs, including fear of negative appearance evaluation, social appearance anxiety, and social physique anxiety, which have demonstrated strong links with eating pathology in adolescent and adult samples [19, 36, 41]. Although currently understudied in pediatric obesity samples, some work conducted in high school aged adolescents has evinced positive associations between social physique anxiety and drives for muscularity and thinness, which often relate to risk for unhealthy dieting, food preoccupation, and body dissatisfaction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Since the current investigation indicates fear of negative evaluation is a particularly important social anxiety facet to consider in relation to disordered eating symptoms for youth with obesity, additional research must begin to examine similar constructs, including fear of negative appearance evaluation, social appearance anxiety, and social physique anxiety, which have demonstrated strong links with eating pathology in adolescent and adult samples [19, 36, 41]. Although currently understudied in pediatric obesity samples, some work conducted in high school aged adolescents has evinced positive associations between social physique anxiety and drives for muscularity and thinness, which often relate to risk for unhealthy dieting, food preoccupation, and body dissatisfaction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Social appearance anxiety is the fear of overall appearance evaluation and has been shown to be robustly related to symptoms of anorexia and bulimia nervosa, more so than other facets of social anxiety (Dakanalis et al, 2016; Levinson & Rodebaugh, 2012; Levinson et al, 2013). Further, Koskina, Van den Eynde, Meisel, Campbell, and Schmidt (2011) found that social appearance anxiety is related to global eating disturbance and dietary restraint in the context of bulimia nervosa.…”
Section: Social Anxiety and Binge Eatingmentioning
confidence: 99%
“…anorexia nervosa, bulimia nervosa, or binge-eating disorder). While there is a close association between social appearance anxiety and EDs (Dakanalis et al, 2016; Levinson et al, 2013; Levinson and Rodebaugh, 2012), thus far little research has focused on social appearance anxiety to examine the relationship between body esteem and EDs; the present study therefore advances our understanding of the development of EDs.…”
Section: Discussionmentioning
confidence: 88%
“…Koskina et al (2011) revealed that compared with healthy control groups, subjects with bulimia nervosa had more social appearance anxiety. More recently, social appearance anxiety has been found to be more strongly linked to EDs, such as anorexia and bulimia nervosa, relative to other facets of social anxiety (Dakanalis et al, 2016; Levinson and Rodebaugh, 2012; Levinson et al, 2013). Brosof and Levinson (2017) investigated 300 women, and found that social appearance anxiety not only predicted binge eating at baseline but also mediated the relationship between concern over mistakes and binge eating across 6 months.…”
Section: Theoretical Review and Research Hypothesesmentioning
confidence: 99%